#TITLE_ALTERNATIVE# - Subadra (NIM : 13611022), Agus
Composite is a combination of two or more materials that form different properties of the constituent materials. One of eco-friendly composite is a thermoplastic composite from natural fiber, because it can be recycled. One of natural fiber which is available in large quantities and easy growth is bamboo. Indonesia is a tropical country, very potential to cultivate bamboo as a natural fiber material for composites, due to the strength of bamboo fiber that is closer to glass fiber. Bamboo is also known as a natural composite which is available in a nature. It contains vascular bundles and tissues which are like fibers and matrices. Bamboo also has many advantages than other natural fiber materials. The advantages of bamboo are easy to grow and fast growth, have a high resistance against wind, low prices and provide benefits to the environment. Bamboo structure is very efficient structure in receiving load, so the bamboo has a high resistance against wind. Bamboo fibers and nodes provide an important role in receiving load. The layout of this structure is similar to the concept of the fuselage structure which consists of frames and stringers. Structures, devices, systems that imitate nature is known as biomimetic. Biomimetic studies on bamboo are an interesting thing to do. Therefore, the investigation on bamboo is done as a preliminary study of biomimetic bamboo structure. This preliminary research was conducted to look at the characteristics and mechanical properties of bamboo. Experimental tests are conducted in order to gives a consideration for using bamboo as natural fiber materials. There are three experiments conducted in this research, bamboo structure compressive test, tensile test and compressive test along fiber (longitudinal) direction. Compressive tests on bamboo structures were performed to see the compressive strength and buckling characteristics of the bamboo structure. The compressive tests of bamboo structure are performed at different configurations, i.e., internode, node and side node. Meanwhile, tensile and compressive tests on bamboo specimens along fiber direction is done to know the mechanical properties of bamboo material. Experimental tests conducted on two types of tropical bamboo in Indonesia, Gigantochloa apus and Gigantochloa pseudoarundinacea. Based on the research, the ability of bamboo structure in receiving compressive load is varied. Results from three different cutting configurations between bamboo structures did not produce the same trend. This is due to the effect of size, cutting position and bamboo age. Meanwhile, tensile and compressive test results of bamboo specimens along fiber direction provide more consistent value. Reliability based on Weibull distribution gives a good result. Tensile and compressive strength of G. Pseudoarundinacea are 280 MPa and 43 MPa, respectively with 90% reliability. Meanwhile, tensile and compressive strength of G. Apus are 180 MPa and 28 MPa, respectively with 90% reliability. The experimental results indicate that tensile and compressive tests performed on bamboo specimens along fiber direction have been successful. Meanwhile, compressive test on bamboo structure with three different cutting configuration have not shown consistent results. It is due to size factor, cutting position, age of the bamboo and the number of specimens tested.